Strategi Merek Pada Keripik Pisang - Ameilia, Deva Ameilia; Hidayah, Nenden Restu; Susena, Karona Cahya (Jurnal Kewirausahaan & Inovasi, 2023)
Brand strategy is the management of a brand or brands where there are various         activities or activities that manage all elements that have the goal of forming a brand or brands.Brand strategy implementation is carried out in several steps, such as creating a brand identity for banana chips and using social media. Brand identity is made to introduce the banana chip brand more clearly and up to date in the market, while the use of social media is done so that consumers can easily recognize and remember the chip brand and give a positive image to the brand.